Technical Artifacts: Which approach is best? - Monterroza Ríos, Álvaro David (Estudios de Filosofía, 2011)
The paper describes the strengths and weaknesses of the three dominant approaches in the ontological theories of technical artifacts, which are the approaches: (1) functional, (2) intentional and (3) dual. I will show it is not appropriate to focus solely on “functions” or “intentions” to formulate a general theory of artifacts. The dual approach should not miss out on material and structural elements, but must also be consistent with symbolic elements and context in which humans live.